Introduction: 8 years of the Labor Reform: Critical Reflections and Perspectives on Class Struggle and Precariousness (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
The text introduces the 48th edition of the ESA OAB SP Scientific Journal, analyzing the eight years of the Labor Reform (Law No. 13,467/2017). The author highlights that the reform shifted the balance of power in favor of capital, promoting a private contractual logic that hollows out worker resistance. The edition compiles 15 articles examining themes such as intermittent contracts, telework, algorithmic subordination, and access to justice in the post-reform scenario. (Received: July 2025 | Accepted: September 2025).
Keywords: Labor Reform; Social Justice